Rethinking strategic planning. Part I: Pitfalls and Fallacies. Part II: New Roles for Planners. - MINTZBERG, Henry (1994)
Examines what went wrong with strategic planning, and the lessons that could be learnt from that experience - both about the management processes and about the planners. Concludes that strategic planning has never been strategy making, which is a process of synthesis, not just analysis.